Pelaksanaan Kegiatan Pembelajaran Membaca, Tulis Dan Hitung (Calistung) Untuk Meningkatkan Kemampuan Matematis Santri TPA Al-Ukhwah di Desa Tanjung Deah, Aceh Besar - Lisma Novita; Zainal Abidin (Jurnal Riset dan Pengabdian Masyarakat, 2021)
This community service activity is motivated by the low level of mathematical ability of TPA children in learning to read, write and count. This activity aims to increase the mathematical ability of Al-Ukhwah TPA children in the fields of reading, writing, and arithmetic. The implementation of this activity was carried out using descriptive research methods with a qualitative approach. The findings in this service are 1) Knowing the importance of learning to read, writing and counting, 2) Researchers can carry out this activity in several ways, including designing methods or strategies and teaching materials, providing motivation and teaching, and selecting assignments to be given, 3) Reading, writing and arithmetic activities can improve children's mathematical abilities.